(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
In this article, proposals and recommendations have been developed to provide a defense counsel who can adequately protect the rights and freedoms of people in cases when a socially dangerous act is committed by mentally retarded or mentally disturbed people or persons whose mental state is temporarily disturbed after committing a socially dangerous act, as well as that, some problematic issues arising in connection with the participation of the defense counsel in the judicial investigation practice are developed.